BioMEMS and Nanotechnology III 2007
DOI: 10.1117/12.759259
|View full text |Cite
|
Sign up to set email alerts
|

Feature extraction of performance variables in elite half-pipe snowboarding using body mounted inertial sensors

Abstract: Recent analysis of elite-level half-pipe snowboard competition has revealed a number of sport specific key performance variables (KPV's) that correlate well to score 1 . Information on these variables is difficult to acquire and analyse, relying on collection and labour intensive manual post processing of video data. This paper presents the use of inertial sensors as a user-friendly alternative and subsequently implements signal processing routines to ultimately provide automated, sport specific feedback to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…In the gym, sensor data from balance board training [14,15] has been used to provide feedback on the performance quality. Furthermore, body-worn inertial sensors have been used for the assessment of (professional) athletes in sports such as snow-boarding [16], swimming [17] and running [18]. Beyond applications in sports, similar systems have been employed to assess professional skills, e.g.…”
Section: Automatic Assessment Of Physical Activitymentioning
confidence: 99%
“…In the gym, sensor data from balance board training [14,15] has been used to provide feedback on the performance quality. Furthermore, body-worn inertial sensors have been used for the assessment of (professional) athletes in sports such as snow-boarding [16], swimming [17] and running [18]. Beyond applications in sports, similar systems have been employed to assess professional skills, e.g.…”
Section: Automatic Assessment Of Physical Activitymentioning
confidence: 99%
“…Recently the use of MEMS technology based miniature inertial sensors, accelerometers and gyroscopes, has got a lot of interest in sports applications [2,3]. Mainly this has happened because these sensors are independent from other signal sources (they are passive in that respect).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that air time can be objectively calculated using video-based analysis and that there is a significant and large linear relationship (r 5 0.5670.26, Po0.001, r 2 5 0.31, Standard error of the estimate (SEE) 5 4.60, n 5 30) between total air time and an athletes subjectively-judged score during two FIS World Cup half-pipe snowboarding competition finals held in Bardonecchia, Italy in 2005 [3]. The two-pass signal-processing technique promoted within this study was able to detect 100 per cent of the aerial acrobatic maneuvers performed [3]. This is a result of the labor-intensive nature of the manual post-processing of video data and the subsequent time delay in information feedback.…”
Section: Automated Objectivity: Air Timementioning
confidence: 99%
“…The components of air time and amplitude, however, are currently assessed subjectively by elite-level coaches and competition judges when providing performance feedback to athletes. We therefore promoted the use of microtechnology to provide automated objective feedback on air time and recently showed that air time can be accurately and reliably calculated using inertial sensor output (provided by tri-axial accelerometers) and basic signal-processing techniques [3]. It is believed, however, that the use of video analysis to objectively calculate information on air time during halfpipe snowboarding would be difficult to incorporate on a routine basis.…”
Section: Automated Objectivity: Air Timementioning
confidence: 99%